The Correlations Between Students’ Interest and Parental Guidance with Learning Outcome of Social Science - Rahmawati, Isa Ansori, Nuzulia (Elementary School Teacher, 2018)
This investigation was aimed at finding out the relations between students’ interests and parents’ guidance with grade V students of SD Gugus Melati of Semarang City’s social science learning outcome. This is correlational study. The targeted population consisted of 145 grade V students of SD GugusMelati of Semarang City, and proportional random sampling, I choose 43 students as samples. The data were collected through questionnaire fulfilling, interviews, and documentation. While I used students’interests questionnaire and parental guidance interview sheet as research instruments. I applied normality test and linearity test as the requirement analysis. And I applied simple linear regression analysis, multiple linear regression analysis, and coefficient of determination. The study shows that:(1) the relations between students’ interestsand social science learning, I got score: rtotal is bigger than rtable(0.682 > 0.301) Ha is acceptable, (2) the relations between parents’ guidance and social science learning outcome, I got score:rtotal is bigger than rtable (0.819 > 0.301) Ha is acceptable, (3 out the relations between students’ interests and parents’ guidancewith students’social science learning outcomeI got score:rtotal is bigger than rtable (0.739 > 0.301), thus Ha is acceptable.